(untitled) (Journal of Bio-Science, 2015)
Context: Recent reports of media have brought great attention to the problem of formalin used by whole sellers and venders in preserving fish. It is evident from several studies that fish items in different markets in Bangladesh are treated with formalin for preservation which is highly hazardous and carcinogenic chemical. Objectives: The study was undertaken to determine the presence of formalin in fishes collected from various wet markets of Tangail and Tongi town. Materials and Methods: From 12 selected wet markets, various species of fishes were collected and presence of formalin was detected using the formalin detection kit in fish developed by Bangladesh Council of Scientific and Industrial Research (BCSIR). Results: It was found that 16 fishes were formalin contaminated out of 192 fish samples in which 0% in Santosh bazar, 11.11% in Soi ani bazar, 13.33% in Park bazar, 14.81% in Old bus stand bazar, 0% in Chara bari bazar and 12.82% in New bus stand bazar of Tangail town. On the other hand, 33 formalin contaminated fish out of 171 were obtained in which 0% in Coto bazar, 20% in Gazipura bus stand bazar, 37.5% in Chourasta bazar, 0% in Boro bari bazar, 36.36% in CheragAli bazar and 20% in Tongi bazar of Tongi town. The study indicates that almost 8.33% of fish samples in Tangail town and 19.29% of fish samples in Tongi town were formalin contaminated. Conclusion: The present study revealed that in Tangail town 75% imported fish and 25% local fishes were formalin contaminated whereas in Tongi town, 82% imported fishes and 18% local fishes were formalin contaminated. DOI: http://dx.doi.org/10.3329/jbs.v21i0.22518 J. bio-sci. 21: 43-49, 2013